Cooperative and Creativity Building in Unison Singing - Ruata, Isabella Christy; Utomo, Udi; Hartono, Hartono (Universitas Negeri Semarang, 2018)
This research analyses the building of cooperative and creative character in the teaching of singing unison. This research employed the qualitative method. The data of this research were obtained from observation, interview, and documentation. The analysis of the data was in the sequence of data reduction, data presentation, and data verification or conclusion. The finding showed that the teaching of singing in unison instil the character of cooperativeness when the students play different musical instruments together. Besides, cooperativeness is also realised when the students sang that in the group. In teaching arts, the song also contained the value of creativity of which the students can solve specific task given by the teacher and when the students developed the rhythmic pattern of the song with a traditional instrument. The findings implied education, particularly musical education.